Efek Kombinasi Terapi Edukasi dan Strengthening Exercise Terhadap Peningkatan Activity Daily Living dan Range of Motion Pasien Osteoarthritis Knee - Yohanes Deo Fau; Byba Melda Suhita; Prima Dewi Kusumawati; Nurwijayanti Nurwijayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Osteoarthritis is a disease that is ranked eleventh worldwide that causes disruption to daily activities and is a major global health problem. Strengthening exercises are muscle strengthening exercises that are considered effective in knee osteoarthritis rehabilitation programs. Education in health services has a strong scientific evidence base in assisting the process of health services, especially knee osteoarthritis, which in essence is a treatment that is prioritized from the start of treatment to evaluation. The purpose of this study was to analyze the educational effect of the strengthening exercise combination treatment on changes in activity daily living and range of motion in conditions of knee osteoarthritis. There were 26 subjects in this study and they were divided into 2 groups, namely 13 people with education on the strengthening exercise combination treatment and 13 people with electrotherapy as controls. Activity daily living was measured using the Western Ontario and McMaster Universities Osteoarthritis Index WOMAC scale and range of motion was measured using a goniometer. The p-value of the parried sample t-test was <0.05 for both the treatment and control groups. The p-value of the independent sample t-test was <0.05, meaning that there was a difference in the effect of the two groups, where the combination strengthening exercise treatment education had more effect. It was concluded that the combination strengthening exercise treatment education greatly influences changes in activity daily living and range of motion in knee osteoarthritis conditions.Keywords: knee osteoarthritis; treatment education; strengthening exercises; daily living activities; range of motion ABSTRAK Osteoartritis merupakan penyakit yang menduduki peringkat sebelas penyakit diseluruh dunia yang menyebabkan gangguan aktifitas keseharian dan menjadi salah satu masalah utama kesehatan global. Strengthening exercise adalah latihan penguatan otot yang dianggap efektif dalam program rehabilitasi knee osteoarthritis. Edukasi dalam pelayanan kesehatan memiliki dasar bukti ilmiah yang kuat dalam membantu proses pelayanan kesehatan khususnya knee osteoarthritis yang pada intinya adalah suatu treatment yang diprioritaskan diawal penanganan sampai pada evaluasi. Tujuan penelitian ini adalah untuk menganalisis pengaruh edukasi treatment kombinasi strengthening exercise terhadap perubahan activity daily living dan range of motion pada kondisi knee osteoarthritis. Subyek penelitian ini adalah 26 dan dibagi menjadi 2 kelompok yaitu 13 orang dengan edukasi treatment kombinasi strengthening exercise dan 13 orang dengan elektroterapi sebagai kontrol. Activity daily living diukur menggunakan skala Western Ontario and McMaster Universities Osteoarhtritis Index WOMAC dan range of motion diukur menggunakan goniometer. Nilai p dari paried sample t-test adalah <0,05 baik untuk kelompok perlakuan maupun kelompok kontrol. Nilai p dari independent sample t-test adalah < 0,05, berarti ada perbedaan pengaruh dari kedua kelompok, dimana edukasi treatment kombinasi strengthening exercise lebih berpengaruh. Disimpulkan bahwa edukasi treatment kombinasi strengthening exercise sangat berpengaruh terhadap perubahan activity daily living dan range of motion pada kondisi knee osteoarthritis.Kata kunci: knee osteoarthritis; edukasi treatment; strengthening exercise; activity daily living; range of motion